PERANAN SISTEM INFORMASI AKUNTANSI DALAM PENGAMBILAN KEPUTUSAN MANAJEMEN PADA PT. ABADI MEDAN JAYA JAPARIS - Indah Puspita Sari Bulolo; M. Nursidin (UNIVERSITAS DHARMAWANGSA, 2021)
The role of information systems is very important for companies to be able tosupport every operational activity and assist in the decision-making process. Therehave been many companies that use information systems to support their businessprocesses so that by using this information system, the company's competitiveadvantage can be achieved. The formulation of the problem in this study is how therole of accounting information systems in management decision making at PT.Abadi Medan Jaya Japaris ?. The research objective is to identify and analyze therole of accounting information systems in management decision making at PT.Abadi Medan Jaya Japaris. This study uses simple linear regression analysis,determination test and t test, with the help of the SPSS version 20.00. Based on theresults of hypothesis testing, it shows that t count > t table, namely 18.905>2.03951, then H0 is rejected and H1 is accepted, which means that the accountinginformation system variable has a positive and significant effect on the decisionmaking variable at PT. Abadi Medan Jaya Japaris. Which means that theaccounting information system plays an important role for management in makingdecisions at PT. Abadi Medan Jaya Japaris. In addition to the determination test,it is known that the percentage of the relationship between variable X accountinginformation system and variable Y is used. The determination test is used todetermine the influence of the accounting information system on decision makingof 0.920 or 92% while the remaining 0.08 or 8% is influenced by other factors thatare not researched in this study